Does simulation have a role in palliative medicine specialty training?. Issue 4 (17th June 2016) - Walker, Lucy N; Russon, Lynne
Abstract : Simulation training has been adopted by other industries, particularly aviation, for many years. With patient safety on every agenda, more recently there has been considerable interest and investment in its use for the acute medical specialities. Evidence in palliative medicine, for the use of simulation is mainly limited to advanced communication skills but little is described about its use in developing acute clinical skills. This article describes how in the Yorkshire and Humber Deanery a simulation training day was set up for Palliative Medicine specialty trainees, to assess their knowledge and develop the skills required to deal with acute medical emergencies, as described in the specialty training curriculum for palliative medicine. Scenarios included opioid toxicity, acute left ventricular failure, anaphylaxis, hypoglycaemia and massive haemorrhage. The set up and scenarios are described, along with the mechanisms for delivering feedback. This method of training received positive feedback from trainees and facilitators. The advantages, limitations and potential future role for high-fidelity simulation training for medical trainees and the wider multidisciplinary palliative care team are discussed.